Development framework for district: a systems approach - Verma Kush
The cutting edge of all developmental activity is the district. The best plans are to go away is the delivery system is not responsive, knowledgeable and efficient. Thus need of the hour is clear communication channels, a motivated workforce, constant monitoring and self corrective mechanisms
Keywords: Delivery System; Development Administration; District Administration